FIRST RECORD OF RED ALGAE POLYSIPHONIA SUBTILISSIMA (MONTAGNE, 1840) (FAMILY: RHODOMELACEAE) COLLECTED FROM KARACHI COAST PAKISTAN (NORTHERN ARABIAN SEA). - Quratulan Ahmed,; Qadeer Mohammad Ali,; Fikrat. M. Hassan,; Ateeqa Baloch,; Shumaila Mubarak,; Iqra Shaikh, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study presents a detailed morphology and taxonomic study of Polysiphonia subtilissima collected from Abdul Rehman Goth, Karachi coast, Pakistan. Polysiphonia is a filamentous heterotrichous red algae, characterized by its branching structures and attachment mechanisms. P. subtilissima is notable for its broad salinity tolerance and wide distribution across marine and freshwater ecosystems. This research provides an in-depth examination of the internal and external structures of P. subtilissima, contributing to its systematic study and documenting its first recorded occurrence in Pakistani coastal areas, bordering the northern Arabian Sea. The findings enhance the understanding of the species taxonomy and its ecological role in the region.